Ethics of Lecturers at the State Islamic University of North Sumatra - Balqis Maulida; Ramadhana Mutia Eka Ismail; Irwansyah Alfaqih (Education Achievement: Journal of Science and Research, 2024)
Higher education as a place for the implementation of education has the duty and responsibility to lay the foundations of moral values. Lecturers are a profession that requires expertise and technical knowledge enough to support their professionalism. Lecturers have duties and responsibilities that are manifested in the tri dharma of higher education, including education and teaching, research and community service. For this reason, lecturers in carrying out their duties and responsibilities must always uphold ethics. Because ethics has a role in ensuring the quality of services provided to the academic community. This study uses a qualitative method and is completed with a sociology of knowledge approach. The use of this sociological approach of knowledge is a way to achieve relevance between the construction of righteousness that is made to be able to explain the data that is used as a step and effort in solving this research so that this research can provide an explanation that is able to influence the understanding of the reader. In the treatment of lecturers who often interact between lecturers and students, both in providing lessons or services carried out by lecturers to students. At UIN North Sumatra, it can be categorized that the lecturers in this university provide influence and also satisfactory service not all, but this is able to give a view on the ethics of lecturers in handling problems and student lessons with pedagogic competence and professional attitudes possessed by the lecturers. Ethics for lecturers at UIN North Sumatra universities are only a few and only a few. But basically, the average lecturer at UIN North Sumatra University has service ethics and coaching lessons can be met with all the needs of the students themselves.